Biomass, Stem Volume, and Carbon Sequestration Based on Allometric Equations for Populus deltoides W. Bartram ex Marshall. Planta- tions (A Study of Guilan, Iran): Investigation of Biomass, Volume, and Carbon Sequestration Allometric Equations - Abedi, Roya (Polish Journal of Natural Sciences, 2023)
Populus deltoides Marshall. is one of the most important economically (wood production), environmentally (biomass production and carbon sequestration), and fast-growing species in plantations. Therefore, this study aimed to investigate biomass, volume, and carbon sequestration models according to age by using the stem analysis method in poplar plantations in five regions of Guilan province. Measurement features included DBH and the total height of all trees in two plots with one hectare in each region. 30 trees were randomly selected in different diameter classes and cut down and the discs were obtained in order to stem analysis. The annual rings of discs were counted, ages at different tree heights were obtained, and the diameter of the annual rings was measured to determine the annual diameter and volume increments. Carbon measurement, volume measurement of wood, and volume conversion to weight ratio were calculated. Finally, regression analysis was performed by the relationship between volume and biomass growth by age based on the highest coefficient of determination and minimum standard error. The results showed that the nonlinear models were able to show the highest coefficient of determination (R2=0.93-0.99) and the least standard error of the relationship between these characteristics. These models can be applied for the annual assessment of poplar plantations in carbon sequestration and optimal management for achieving sustainable development of the various plantations.